Efektivitas Media Pembelajaran dalam Meningkatkan Kemampuan Berbicara Bahasa Arab Siswa di Madrasah Ibtidaiyah - Yufi Mohammad Nasrullah (Jurnal PGSD UNIGA, 2023)
Proficiency in speaking the Arabic language holds a significant place in the curriculum of elementary Islamic schools (madrasah ibtidaiyah). Nonetheless, students often face challenges in honing this skill. Hence, this study aims to examine the application of instructional media in boosting students' Arabic speaking prowess within the context of madrasah ibtidaiyah. The research employs a classroom action research approach, involving students in a sequence of learning activities supported by diverse instructional media. The outcomes of the study reveal that the strategic use of instructional media effectively contributes to the enhancement of students' Arabic speaking abilities. This is evidenced by their heightened active participation, expanded vocabulary utilization, and increased self-assurance in conversing in Arabic.Keywords: Arabic language, instructional media, speaking skills, elementary Islamic schools.